Six dots : a story of young Louis Braille - Bryant, Jennifer; Kulikov, Boris, 1966- (New York : Alfred A. Knopf, 2016)
Looks at the childhood of Louis Braille and his creation of the Braille writing system for the blind.
Includes bibliographical references.
School Library Journal starred, September 2016.
Bulletin of the Center for Children's Books starre, July 2016.
Pub Weekly, August 2016.
Booklist, June 2016.
Horn Book, November 2016.
Keywords: Braille, Louis, -- 1809-1852 -- Childhood and youth -- Juvenile literature; Braille, Louis, -- 1809-1852.; Braille, Louis, -- 1809-1852.; Blind teachers -- France -- Biography -- Juvenile literature; Braille -- Juvenile literature; Blind; Teachers; Braille; Blind -- France -- Biography; Teachers -- France -- Biography; Braille; Teachers -- Biography; Braille